A new genus and species of Aoridae (Amphipoda, Senticaudata), Propejanice lagamarensis gen. nov. sp. nov. from Brazil - Myers, Alan A.; Desiderato, Andrea (Zootaxa, 2019)
A new monotypic genus of aorid amphipod Propejanice gen. nov. is described and figured from material collected in Brazil. The single species, P. lagamarensis sp. nov. was collected from artificial plates suspended in the sea in Paraná and Sao Paulo States, Brazil. The new genus appears to be morphologically closest to the genus Janice Griffiths, 1973 from Moçambique, from which it differs in the carpochelate male gnathopod 1. Both genera are phylogenetically close to the genus Grandidierella Coutière, 1904.